Taxonomia integrativa de Allobates (anura: aromobatidae) do Sudoeste da Amazônia brasileira, com delimitação de três espécies novas - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Anurans of the genus Allobates (Dendrobatoidea, Aromobatidae) comprise a monophyletic group of small leaf litter inhabitants of tropical forests, which are distributed from the western Andes to eastern Brazil. The main challenge for the alpha taxonomy of this genus is related to the pronounced conservatism of external morphological characters between species, which are usually used as diagnoses and which strongly contrast with a remarkable bioacoustic and genetic disparity among populations. Using what is conventionally called integrative taxonomy, a comprehensive method to delimit and describe taxa integrating information from different classes of characters, Allobates lineages from southwestern Amazonia, in the Brazilian state of Acre, were investigated using molecular, bioacoustic, and morphological data of adults and tadpoles. In the first chapter, we describe Allobates velocicantus for the Juruá region, which is extremely important for the conservation of several biological groups. This taxon is genetically and morphologically different from the other species of Allobates, notably by its advertisement call, which is considered structurally unprecedented for the genus. In the second chapter, we describe Allobates albiventris for the headwaters of the Purus river. This species was confused and misnamed, for a long time, as Allobates gasconi, in several Amazonian localities. In the third chapter, we describe a new species belonging to the trilineatus complex, widely distributed in Amazonia and whose diversity is underestimated, with several species erroneously determined and lacking formal description. This thesis contributes not only to the taxonomy of Allobates, but also to a better understanding of the evolution and biogeography of the still underestimated southwestern Amazonian biodiversity.
Keywords: Anuros - Conservação; Zoologia - Classificação; Biodiversidade - Conservação; CIENCIAS BIOLOGICAS: ZOOLOGIA; Acre; Bioacústica; Biologia molecular; Dendrobatoidea; Inambari